Pengaruh Aturan Asimilasi di Rumah dalam Menekan Laju Penyebaran Covid 19 Terhadap Narapidana di Lapas Kelas II A Parepare - Syahril, Muh. Akbar Fhad; Ambarwati, Auliah (JUSTISI, 2023)
This assimilation program is a right obtained by all prisoners and children who meet the requirements. The purpose of this study is to answer 2 (two) main problems, namely the extent to which the implementation of the rules of assimilation and the right of integration at home for prisoners in Class II A Prison in Parepare City, and can the implementation of the rules of assimilation and the right of integration at home for prisoners have an effect in suppressing the spread of Covid-19 at Class II A Prison in Parepare City. This research is an experimental research that uses empirical or non-doctrinal legal research with a quantitative approach to prisoners and their warden staff Rules; Assimilation; Covid-19 at Class II A Prison in Parepare City. This assimilation aims to measure the level of citizen protection as an influencing variable (X1), equal rights for prisoners as a variable (X2), and the provision of health insurance for all citizens (X3) in suppressing the spread of the covid outbreak as the dependent variable (Y). in the Class IIA Prison in Parepare.